The urgency of vaccination COVID-19 in children - Supriyadi, Supriyadi (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2021)
The incidence of COVID-19 disease is much lower in children. Because the incidence and burden of COVID-19 disease are low in children, vaccination should not be done primarily for their self-protection but for communities, especially parents or high-risk individuals. Therefore, any vaccine should be thoroughly tested and proven safe before giving it to children to respect the risk-benefit balance.